2021
DOI: 10.1038/s41598-021-02988-4
|View full text |Cite
|
Sign up to set email alerts
|

RAM cannula with Cannulaide versus Hudson prongs for delivery of nasal continuous positive airway pressure in preterm infants: an RCT

Abstract: Nasal continuous positive airway pressure (nCPAP) is the standard non-invasive respiratory support for newborns with respiratory distress. Nasal injury is a common problem with the interfaces used. To compare the incidence and severity of nasal injury in neonates with respiratory distress and supported on nCPAP with Hudson prong or RAM cannula with Cannulaide, a semipermeable membrane. This is an open-label, parallel-arm, gestational age-stratified, bi-centric, randomized control trial including neonates betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Of the 105 studies identified during the systematic search of the literature, a total of six studies were included (RCTs: 3 studies (Maram 2021, Hochwald 2021, and Gokce 2021) ( n = 521); [ 24 , 25 , 26 ] observational studies: 3 studies (Singh 2018, Sharma 2020, Drescher 2018) ( n = 138)) [ 21 , 23 ]. The PRISMA flow is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 105 studies identified during the systematic search of the literature, a total of six studies were included (RCTs: 3 studies (Maram 2021, Hochwald 2021, and Gokce 2021) ( n = 521); [ 24 , 25 , 26 ] observational studies: 3 studies (Singh 2018, Sharma 2020, Drescher 2018) ( n = 138)) [ 21 , 23 ]. The PRISMA flow is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow is depicted in Figure 1 . The three RCTs had enrolled neonates born at a gestational age of 28–34 weeks [ 24 , 25 , 26 ]. Two of the RCTs (Gokce 2021 and Hochwald 2021) [ 24 , 25 ] used NIPPV as the NRS modality, and one (Maram 2021) used CPAP [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations